Educational technology and television in Brazil - Angelini, Arrigo Leonardo (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
This paper presents some recent developments in educational technology related to educational psychology, emphasizing some significant facts regarding the introduction of educational television in Brazil.